Clostridium difficile Cell Attachment Is Modified by Environmental Factors - Waligora, Anne-Judith (American Society for Microbiology (ASM), 1999)
Adherence of Clostridium difficile to Vero cells under anaerobic conditions was increased by a high sodium concentration, calcium-rich medium, an acidic pH, and iron starvation. The level of adhesion of nontoxigenic strains was comparable to that of toxigenic strains. Depending on the bacterial culture conditions, Vero cells could bind to one, two, or three bacterial surface proteins with molecular masses of 70, 50, and 40 kDa.